Anti-inflammatory and Antioxidant Effects of HV Prostate Capsule (HVPC) in Rats with Induced Benign Prostatic Hyperplasia - Ngoc Bich Son Le; Thi Thanh Nhan Le; Van Hung Nguyen; Tu Bui; Thao Phuong Thi Nguyen; Hoang Ngan Nguyen; Viet Van Chau; Dao Cuong To (Current Practice in Medical Science Vol. 11, 2022)
HV prostate capsules (HVPCs) are a Vietnamese herbal prescription drug used to treat benign prostatic hyperplasia (BPH), but its anti-inflammatory and antioxidant mechanisms are not fully understood. This study examined the anti-inflammatory and antioxidant activities of HVPC in white rats with induced BPH. The anti-inflammatory and antioxidant effects of HVPC were tested in a rat model of BPH. The inflammatory cytokines interleukin-8 (IL-8) and tumor necrosis factor \(α\) (TNF-\(α\)) were measured in serum and prostate tissue using an enzyme-linked immunosorbent assay (ELISA) kit. The antioxidant effect of HVPC was evaluated based on the identification of superoxide dismutase (SOD) activity and malondialdehyde (MDA) levels in the blood and the prostate gland. HVPCs at 700 mg/kg/day and 1400 mg/kg/day provided good anti-inflammatory effects in a rat model of BPH and reduced inflammatory cytokines IL-8 and TNF-\(α\) in serum and prostate tissue. This capsule also exhibited antioxidant effects on rats causing BPH by increasing the SOD activity in serum and reducing the MDA content in serum and prostate tissue. HVPC was found to reduce the absolute and relative prostatic weight and improve prostate histopathology. HVPC reduced inflammation of the prostate gland, proliferation of ductal cells, and compression of the gland parenchyma.